The relationship between a measure of Palmar sweat and swimming performance - Nideffer, R. M.; Yock, T. J. (Journal of Applied Psychology, 1976)
Male varsity swimmers (N = 12) had their performances ranked by the coach in the final five intercollegiate meets of the season. Those rankings were correlated with Palmar sweat readings. A negative relationship between the two measures was revealed. As Palmar sweat readings rose, performance ratings deteriorated. This shows the negative effects of emotional arousal on swimming performance. [It should be realized that the swimmers in this case were not necessarily of an elite category. Similar findings in collegiate athletes have been reported for wrestlers (Barry, G. S. (1979). The relationship of pre-competition arousal assessments to self-perceived performance competencies in collegiate wrestlers. Unpublished master's thesis, Lakehead University, Ontario, Canada) and basketball players (Fiorini, A. (1978). The relationship of pre-game arousal assessments to self-perceived performance competencies in male collegiate basketball players. Unpublished master's thesis, Lakehead University, Ontario, Canada).] Implication: Excessive emotional arousal can cause performance deterioration. However, with instruction and skill development that is associated with controlling the energizing properties of high emotional arousal, performances can be benefited. In some sports (e.g., power lifting) it is essential to have high levels of emotional arousal. Athletes should be aroused to the level that they have learned to control.